The lives of the brain human evolution and the organ of mind - Allen, John S. (John Scott), 1961- (Belknap Press of Harvard University Press, 2009)
Though we have other distinguishing characteristics (walking on two legs, for instance, and relative hairlessness), the brain and the behavior it produces are what truly set us apart from the other apes and primates. And how this three-pound organ composed of water, fat, and protein turned a mammal species into the dominant animal on earth today is the story the author seeks to tell in this book. Adopting what he calls a bottom-up approach to the evolution of human behavior, the author considers the brain as a biological organ; a collection of genes, cells, and tissues that grows, eats, and ages, and is subject to the direct effects of natural selection and the phylogenetic constraints of its ancestry. An exploration of the evolution of this critical organ based on recent work in paleoanthropology, brain anatomy and neuroimaging, molecular genetics, life history theory, and related fields, this book shows us the brain as a product of the contexts in which it evolved : phylogenetic, somatic, genetic, ecological, demographic, and ultimately, cultural-linguistic. Throughout, the author focuses on the foundations of brain evolution rather than the evolution of behavior or cognition.